As representações sociais dos Conselheiros Municipais de Assistência Social do Município de Ponta Grossa – PR sobre os beneficiários do Programa Bolsa Família - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The following dissertation proposes to investigate the expressions that highlight the social representations from the social assistence municipal counselors in the municipality of Ponta Grossa/PR. The research is qualitative and has exploratory character. The subjects are members of the Municipal Counsel of Social Aid (CMAS/PG). The administration which they took part began in 2016 and ended in 2017.The epistemological basis of this work is marxian, that is, we use Karl Marx‟s dialectical method of historical study, which can be recognized in the featured structure to organize the chapters of this dissertation. The first chapter comprehends a historical resumption, iniciated in the 1980s going through the 1990s and, finally, the period marked by the implementation of the “Bolsa Família” Program , object of this study, in 2003. The objective in establishing such temporal marks is comprehended by Marx‟s category of totality, as well as making the exposition more didactical e better organized. We presented the international political-economic conjuncture, marked with the beggining and development of the neoliberal ideology and its first advances through the countries of Latin America and, finally, in the brazilian context. The second chapter is denoted by data of secondary sources around the aspects of development and social economic profile of the municipality of Ponta Grossa/PR, in relation to the state and national contexts, by consequence. We based ourselves in the marxian category singularity to this constructuion. Indicators of poverty and extreme poverty and Gini‟s index are, then, organized for better comprehension of this scenario. Also, in this chapter, we take back reflections around the so-called counsil manager and present a characterization of the CMAS/PG. Finally, in the third chapter, are: the concept resumption of the Theory of Social Representations, of ideology and systematic presentation of the accomplished interviews with the subjects of this research. In face of what has been analysed in this material, we may conclude that the rooting of the expressions of the RS are around the reproduction, notably ideological, the populista traces still present in Brazil, just as the conservative traces that historically constitute this municipality. And, even with the use of signs considered positives, there are indications of subordinations of classes exerted by the council members interviewed.
Keywords: Representações sociais; Programa Bolsa Família; conselheiros municipais; Assistência Social; Social Representations; Bolsa Família Program; City Counselor; Social Assistance; CNPQ::CIENCIAS SOCIAIS APLICADAS